Детекторный принцип построения искусственных нейронных сетей как альтернатива коннекционистской парадигме - Паржин, Юрий Владимирович (ФОП Петров В. В., 2017)
Искусственные нейронные сети (ИНС) являются неадекватными биологическим нейронным сетям. Эта неадекватность проявляется в использовании устаревшей модели нейрона и коннекционистской парадигмы построения ИНС. Результатом данной неадекватности является существование множества недостатков ИНС и проблем их практической реализации. В статье предлагается альтернативный принцип построения ИНС. Этот принцип получил название детекторного принципа. Основой детекторного принципа является рассмотрение свойства связности входных сигналов нейрона. В данном принципе используется новая модель нейрона-детектора, новый подход к обучению ИНС – встречное обучение и новый подход к формированию архитектуры ИНС.

Artificial neural networks (ANN) are inadequate to biological neural networks. This inadequacy is manifested in the use of the obsolete model of the neuron and the connectionist paradigm of constructing ANN. The result of this inadequacy is the existence of many shortcomings of the ANN and the problems of their practical implementation. The alternative principle of ANN construction is proposed in the article. This principle was called the detector principle. The basis of the detector principle is the consideration of the binding property of the input signals of a neuron. A new model of the neuron-detector, a new approach to teaching ANN - counter training and a new approach to the formation of the ANN architecture are used in this principle.
Detective principle of artificial neural networks construction as alternative of the connectionist paradigme
Keywords: связность; нейроны-анализаторы; входные сигналы; формирование производных характеристик; ассоциативные моды; artificial neural networks; neuron model; detector principle; connectivity